New Neutron Imaging Facility development at the Penn State Breazeale Nuclear Reactor - Kenges Alibek (EDP Sciences, 2021)
Preliminary results of characterization experiments for the New Neutron Imaging Facility (NIF) that is being developed at the Penn State Breazeale Nuclear reactor are presented in the following sections. The methodology of neutron beam characterization described in the American Society for Testing and Materials (ASTM) documents for the neutron imaging systems have been followed to improve the NIF at Penn State to a Category I facility by ASTM designation of quality. Preliminary results showed that our system is capable of producing images of high quality, corresponding to Category I; however, further experiments are needed for full declaration of our facility as such. Additionally, the effective collimation ratio (L/D ratio) of our current system is ∼110 with the capability of improvement to ∼150. The thermal flux at the exit surface of the neutron beam is equal to 5.4 × 106n cm−2s−1 at 1MWth reactor power, which corresponds to the industry comparable value.